Language choice and use among undergraduates at a Malaysian public University - Granhemat, Mehdi (2015)
Multilinguals, consciously or unconsciously are often confronted with having to select one linguistic code over another from within their linguistic repertoires. The choice of a proper linguistic code enables effective communication and could also lead to the promotion of solidarity among interlocutors. The focus of this study was to describe the language choices of the Malaysian undergraduates in the five domains of language use, i.e. education, family, friendship, religion, and transaction. Furthermore, the study aimed to determine whether individual/social factors, such as age, gender, education background, ethnicity, language proficiency and ethnic identity exert any influence on the choice of languages of the Malaysian undergraduates in the investigated domains of language use. Fishman’s (1968,1972a, 1972) views on domain analysis, Giles and Smith’s (1979, 1973) Social Accommodation Theory (SAT), Tajfel and Turner’s (1986) Social Identity Theory (SIT) and Erikson’s Identity Theory were utilized as theoretical bases in order to conduct the study and answer the research questions. Based on a Random Proportional Stratified Sampling Strategy, a total of 498 undergraduate local students in a Malaysian public university were selected as respondents of the study. The respondents mostly belonged to three main ethnic groups, i.e. the Malays, Chinese,and Indians that together comprise Malaysian society. Also some other ethnic minority groups’ respondents as members of the Malaysian society were included in the study. Data about the demographic profiles of the respondents and the choices of languages in the domains of language use was collected through a self administrated questionnaire survey. SPSS software was used to run analyses such as computing mean scores of the respondents’ used languages. Besides, Chi-Square Test was used to find out the relationships between variables. According to the results, the linguistic situation in Malaysia is similar to a diglossic situation. Results of the study also point to the fact that younger generations of Malaysia are highly proficient in all four basic skills of the Malay language and the majority of them are fluent users of the English language as well. The factor of age was found to be a determinant of language use unless in the education domain. Besides, the factors of education profiles and ethnicity were found to be influential in the choice and use of linguistic codes among the Malaysian youths. But gender was not found to be a determinant of language choice at all. Language proficiency was not a determinant of language choice except in case of the Malay language in the religion and transaction domains. In conclusion, it seems that in multilingual contexts the choice of language is a concomitant of any social interaction.